STABILITAS MIKROKAPSUL Lactobacillus acidophilus ATCC 314 TERHADAP PEMANASAN DAN PENYIMPANAN DALAM SELAI BUAH NANAS RENDAH GULA - Diana Lestari; Tiffany Claudya; Rianita Pramitasari (Jurnal Teknologi dan Industri Pangan, 2019)
Fruit jam added with probiotics is an innovation in food product development. In this research, pineapple jam was made not only to increase the economic value of the pineapple but also to add the health properties due to the addition of probiotics (Lactobacillus acidophilus). The objective of the study was to evaluate the stability of L. acidophilus microcapsules ATCC 314 against heating and storage in low sugar pineapple jam. L. acidophilus was microencapsulated with emulsification method using sodium alginate and oil with Tween 80 as the emulsifier. The microcapsules size was 40-60 µm. Microencapsula-tion was found to improve the stability of L. acidophilus upon heat processing. Total healthy cells of the microencapsulated probiotics heated at 40 and 50°C (1.4x107 CFU/mL; 6.9x106 CFU/mL) were higher than the free probiotic cells (7.9x106 CFU/mL; 4.5x106 CFU/mL). The stability of the encapsulated probiotics in pineapple jam at 4°C (14 days of storage) was also better than that of the free cells. Conclusively, micro-encapsulation process with alginate could increase probiotic stability, thus can be considered in probiotic pineapple jam development.